POLICE MEDICAL EMERGENCY RESPONSE TEAM (POLICE – MERT), THE ROYAL THAI POLICE - Deerungroj, Eakalux (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2023)
Thailand encounters many disasters such as floods, storms, fires, mudslides, earthquakes, epidemics, clashes between demonstrators and government officers, and active shooting incidents, causing casualties, property losses, and an enormous impact on the lives of Thai people. One of the important tasks of the public health agency is to help and take care of the injured people, including mitigating the impact that occurs after each disaster. An important problem in medical management, when a disaster occurs, is the coordination between various agencies involved in the event management system related to medical and public health. An important component in the medical incident command system is the Medical Emergency Response Team (MERT), which is a team consisting of personnel from many professions such as doctors, nurses, pharmacists, paramedics, and emergency medical technicians (EMT) who have the knowledge, ability, and expertise to effectively act as a group in tertiary patient caring in disasters. The Ministry of Public Health together with the Thai Association of Emergency Medicine have formed Medical Emergency Response Team since 2008, which was followed by the Ministry of Defence and Bangkok Metropolitan Administration. Police General Hospital under The Royal Thai Police saw the importance of disasters and therefore established Police Medical Emergency Response Team (POLICE – MERT) to prepare for disasters, especially in urban areas such as clashes, active shooting incidents, and fires in high-rise buildings. Thus, the wounded people can be rescued and treated promptly. In case there are numerous casualties, POLICE – MERT can coordinate with other medical centers and transport those injured people. Furthermore, POLICE – MERT may also act as a medical support unit in various fields supporting other national emergency medical operation teams.